Formulación de vehículos a base de Carica papaya y Fragaria vesca para suspensión de medicamentos sólidos en el Servicio de Farmacotecnia del Hospital Belén de Trujillo - Loyola Mendoza, Lorenzo Ricardo (2017)
The present report was aimed at formulating two vehicles based on Carica papaya and Fragaria vesca for the suspension of certain drugs of solid pharmaceutical form of greater rotation in the Hospital Belén from Trujillo. The samples were obtained from Shiran, located in the district of Poroto in Trujillo Province of the region La Libertad; and using the method of aqueous extraction, conditioned in the laboratory of Pharmacognosy in the Faculty of Pharmacy and Biochemistry at Universidad Nacional de Trujillo, the formulation was proceeded, to finally store them at 2 to 8 ° C; consequently, the Carica papaya vehicle formulated, whose organoleptic characteristics were pale orange, sui generis and sweet taste, presented a yield of 193.13%, density of 1.19 g / mL, refractive index of 1.37 and 5.83 of pH. Also, the formulation of the vehicle of Fragaria vesca presented a yield of 106% where the organoleptic characteristics were; red color, sui generis and sweet-sour taste, 1.18 g/mL of density, 1.36 of refractive index and 4.34 of pH. Therefore, the formulated papaya and strawberry have organoleptic characteristics and acceptable density for use in pediatric patients where the appropriate medicament for the obtained pH should be used